Adoption of Kalina cycle as a bottoming cycle in Wayang Windu geothermal power plant. (December 2017) - Prananto, Lukman Adi; Soelaiman, Tubagus Muhammad Fauzi; Aziz, Muhammad
Abstract: We present the study of electricity generation by utilization of the Kalina cycle system (KCS) as a bottoming cycle in the Wayang Windu geothermal power plant. The KCS converts the thermal energy from the waste brine discharged to the earth crust as a heat source. Based on the brine temperature condition, KCS 11 is the most suitable system among others owing to excellent performance at low to mid-regime temperatures. The constraints of the investigation are focused on the consideration of minimum silica saturation index (SSI) standard of the brine, owing to high SiO2 content. The system is optimized based on the most optimum ammonia-water mass ratio of the working fluid. The system can generate 1660.30 kW of electricity from 48 kg/s of unused brine with 13.20% thermal efficiency while maintaining the proper SSI standard. Owing to the nearly zero cost of heat production from the brine, this system can support the electrification of Wayang Windu geothermal power plant.